(untitled) (Journal of the College of Basic Education, 2023)
What motivated me to choose this topic is the lack of studies that focus on aspectsIntellectual studies, especially Palestinian studies. The research included two chapters, the first on the concept of the state.The second is about the Zionist procedures for the establishment of the state. The researcher tried to obtain the sourcesthe main topic on the topic under consideration, despite the many difficulties that the researcher faced.The research dealt with: two topics, an introduction, a conclusion, and a list of footnotes.The first topic included three topics: the first, the religious and historical reasons for the establishment ofThe Zionist State, Dealing with the Origin of the Jews, and the Arguments They InvokeThe legitimacy of the occupation of Palestine and the encouragement of Jews to settle there. The second topic: it is understoodEthnic purity and its historical roots among the Jews, because the Jews are a mother who existed and was created from the race.The Semites and they are God’s chosen people. As for the third issue, it is the racist Israeli character.In Zionist thought, because of the persecution and deprivation that the Jews suffered from, their politicians soughtTo instill in them the racist idea, and the factors that influenced the imprinting of the Israeli personality with the same characteristics.vice.